2021
DOI: 10.1021/acs.est.0c04108
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost Thaw Increases Methylmercury Formation in Subarctic Fennoscandia

Abstract: Methylmercury (MeHg) forms in anoxic environments and can bioaccumulate and biomagnify in aquatic food webs to concentrations of concern for human and wildlife health. Mercury (Hg) pollution in the Arctic environment may worsen as these areas warm and Hg, currently locked in permafrost soils, is remobilized. One of the main concerns is the development of Hg methylation hotspots in the terrestrial environment due to thermokarst formation. The extent to which net methylation of Hg is enhanced upon thaw is, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
0
18
1
Order By: Relevance
“…Although the relationship between the abundance of the hgc A gene and in situ biological methylation is unclear, these results suggest that its potential activity may have been decreased at higher MeHg and SO 4 ‐S concentrations. As groundwater‐rich fens are abundant in the Interior Plains (Ecosystem Classification Group 2009; Quinton et al 2009), they are potentially important external MeHg sources for these lakes, as fens readily convey water in their channels (Quinton et al 2009) and have been previously identified as Hg II methylation hotspots in boreal sites (Gordon et al 2016; Fahnestock et al 2019; Poulin et al 2019; Tarbier et al 2021). Lakes that receive high DOM inputs from their surrounding catchment, as is typical for peatland lakes in the Interior Plains (Olefeldt et al 2013), have also previously been shown to have high MeHg concentrations but low rates of in situ methylation (Bravo et al 2017; Branfireun et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the relationship between the abundance of the hgc A gene and in situ biological methylation is unclear, these results suggest that its potential activity may have been decreased at higher MeHg and SO 4 ‐S concentrations. As groundwater‐rich fens are abundant in the Interior Plains (Ecosystem Classification Group 2009; Quinton et al 2009), they are potentially important external MeHg sources for these lakes, as fens readily convey water in their channels (Quinton et al 2009) and have been previously identified as Hg II methylation hotspots in boreal sites (Gordon et al 2016; Fahnestock et al 2019; Poulin et al 2019; Tarbier et al 2021). Lakes that receive high DOM inputs from their surrounding catchment, as is typical for peatland lakes in the Interior Plains (Olefeldt et al 2013), have also previously been shown to have high MeHg concentrations but low rates of in situ methylation (Bravo et al 2017; Branfireun et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, certain regions in wetlands and lakes are often favorable locations for methylation (Mitchell et al 2008 a ; Branfireun et al 2020). In addition, permafrost thaw in peatlands often leads to land surface collapse, inundation, and increased groundwater interactions, creating Hg II methylation hotspots (Gordon et al 2016; Fahnestock et al 2019; Poulin et al 2019; Tarbier et al 2021).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Remaining reservoirs (soil, snow, ice and air) were estimated from the stocks of Hg (Dastoor et al, 2022;Table 3.8.1 in AMAP (2021), key data for this review are also shown in Table S1) and the best estimates of %MeHg for each environmental compartment (Tables 1 and S1). The MeHg pool in surface soils was estimated by multiplying the total Hg pool by the median %MeHg in surface soils (St. Pierre et al, 2015: 0.82 %) and wetlands (Tarbier et al, 2021: 1.7 %, not impacted by recent permafrost thaw) and assuming a 25 % coverage of wetlands for the Arctic Region (Kåresdotter et al, 2021). Methylmercury reservoirs in snowpack and glaciers were estimated using %MeHg measurements for snow (6.1 %, range: 0.11-11 %; St.…”
Section: How Much Methylmercury Is Circulating In the Arctic Environm...mentioning
confidence: 99%